PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN ARTICULATE STORYLINE MATA PELAJARAN IPA KELAS VIII SMP - Anggel Kristi; Zuliarni Zuliarni (Journal of Pedagogy and Online Learning, 2023)
The development of interactive learning media using Articulate Storylinejis carried out asjan effortjtojhelp teachers in thejlearning process become better, because when learning uses the lecture method, thejusejof power point learningjmediajis only dominated by writing andjthe usejof learning media. teachingjmaterialsjin thejformjof worksheets and textbooks. With interactive learning media using an articulate storyline, it can help teachers in the learning process, so that learning is more interesting for students to follow. Thisjstudyjaims tojproduce ajvalid and practical Articulate Storyline learning media on optical instruments. This type of research is development research or what is known as Research and Developmentj (R&D). jThisjstudy uses the development modeljproposedjby Brag and Gall which is simplified into 5 steps, namely planning, initial product development, product validation, limited trial, and final product. The product developed was assessed by 2 material validators, namely a science subject teacher at SMP N 25 Padang and 2 media validators, namely a lecturer in the curriculum and educational technology department. The assessment ofjthe practicality test was carriedjoutjby 15 grade VIII students of SMP N 25 Padang. Thejproductjvalidity testjresultsjforjthe materialjaspectjare categorized as "very valid" by obtaining an average of 4.2 from the material validator I and obtaining an average of 4.7 from the material validator II. Thejresultsjofjthe validity assessment for thejmedia aspect are categorizedjas "very valid" by obtaining anjaverage of 4.4 from the media validator I and obtaining an average of 4.54 from the media validator II. Thejresultsjofjthe practicality test conducted by 15 grade VIII students at SMPjN 25 Padang werejcategorizedjas "very practical" withjanjaveragejscore of 4.6. learning and asjajlearning resourcejforjstudents.